Ferric Carboxymaltose in the Management of Iron Deficiency Anemia in Pregnancy: A Subgroup Analysis of a Multicenter Real-World Study Involving 1191 Pregnant Women - Prakash Trivedi; S. Chitra; Suma Natarajan; Vandana Amin; Shilpi Sud; Priti Vyas; Meenakshi Singla; Ajinkya Rodge; Onkar C. Swami (Obstetrics and Gynecology International)
Background. Real-world evidence of the efficacy and safety of ferric carboxymaltose (FCM) infusion in Indian pregnant women with iron deficiency anemia (IDA) is lacking. Objective. To assess the efficacy and safety of intravenous (IV) FCM in Indian pregnant women with IDA in 4 weeks in a real-life scenario. Methods. This is a subgroup analysis of our previously conducted retrospective, multicenter, observational, real-world PROMISE study. Data on demographic and hematological parameters, patient-reported adverse events, and physicians’ clinical impressions of efficacy and safety were analysed at 4 ± 1 week. Results. This subgroup analysis included 1191 pregnant women in whom IV FCM resulted in a significant increase in hemoglobin (Hb) by 2.8 g/dL and serum ferritin by 30.03 μg/L at 4 weeks (P<0.001 for both). In 103 pregnant women with severe IDA, there was a significant increase in Hb by 3.6 g/dL (P<0.001), and serum ferritin by 16.96 μg/L (P=0.12). In 978 pregnant women with moderate IDA, significant improvement in Hb by 2.74 g/dL and serum ferritin by 33 μg/L (P<0.001 for both) was noted. Similarly, there was a significant increase in red blood cell count, hematocrit, mean corpuscular volume, and mean corpuscular hemoglobin (P<0.001 for all). In pregnant women with mild IDA (n = 26), Hb increased significantly by 1.99 g/dL (P<0.001). Adverse effects were reported in 8.6% of pregnant women. No new safety signals or serious adverse effects were observed. Based on physicians’ global assessment, good to very good efficacy and safety of IV FCM was noted in 99.2% and 98.6% of pregnant women, respectively. Conclusions. IV FCM rapidly corrected anemia in a short period of 4 weeks with favorable safety in the second and third trimester of pregnancy with all severities of IDA (severe, moderate, and mild). The physicians’ favorable global assessment of FCM’s efficacy and safety in pregnant women with IDA supports its use in daily clinical practice. This trial is registered with CTRI/2021/12/039065.